Negative effects of ghost nets on Mediterranean biodiversity - Perroca, Júlia Fernandes [UNESP] (2022)
Abandoned, lost or otherwise discarded fishing nets (i.e., ghost nets) strongly affect biodiversity in marine ecosystems of numerous localities around the world. Based on videos posted by different people in YouTube™, we accessed the negative effects of these gears in the Mediterranean Sea. We identified 86 species, from 12 groups, in 12 countries within the Mediterranean region (including in the Africa, Europe, and Asia). Of the species entangled in ghost nets, 10 are considered threatened with extinction according to the International Union for Conservation of Nature. Fishes and macrocrustaceans were the most recorded groups entangled in ghost nets. We also identified algae, other invertebrates (i.e., cnidarians, echinoderms, molluscs, poriferans, tunicates) and vertebrates (i.e., turtles and mammals). The larger number of ghost fishing events were recorded in Italy and Turkey. This is the most complete study showing the negative effects of ghost nets on marine biodiversity worldwide, based on data retrieved from digital media. With the available literature, our data are important to implement measures against ghost fishing nets in the Mediterranean Sea.